Somos todxs estrelas pornô?: a produção de subjetividades-vitrine no Cine Majestick (Fortaleza/CE) - Coelho, Juliana Frota da Justa (Universidade Federal de São Carlos, 2018)
The main objective of this thesis is to problematize the production of "showcase-subjectivities" in the porn movie Majestick, located in the downtown of the city of Fortaleza (CE). These subjectivities are assemblages of technologies of subjectivation, such as the architectures, spatialization, temporalization, displacement, and the intersectional and geopolitical spectacularization of sexualities, which make visible practices considered pornographic at the same time as they guard or subvert them. Initially, I discuss the sexopolitics of the construction of the "cinemões" circuit of Ceará's capital, from the family and elitist proposal of the early twentieth century to its gradual pornification in the late twentieth century and the present twenty-first century. Based on two and a half years of fieldwork, fourteen interviews and for what I questioned as a desiring methodology, I discuss the pornographic assemblages in this "cinemão", situating my position as a woman, cis, white, northeastern and middle class researcher, as well as elaborating a critique, from the fieldwork, on the colonization of the body of researchers of the sexualities - mainly of the women researchers - that discards the desires as production of knowledge. The "showcase" - crossed by pornographic networks of the cinemões, which include bodies, architectures, morals, smells, fluids, gradations of light, sounds, diverse substances and other types of stimulants - concerns the spectacularization of sexualities in certain spaces, such as in porn cinemas in Fortaleza, producing porn stars that are not limited to actresses and actors in pornographic films. There is no intention of linking pornography to the total subversion of morally accepted sexual values (since it often ratifies them), but rather to question what kind of pornography (historically associated with obscene jouissance) is organized in these spaces that present themselves in the center of the city of Fortaleza as "cinemas", with emphasis on Cine Majestick.
Are we all porn stars?: The production of showcase subjectivities at the Cine Majestick (Fortaleza / CE)
Keywords: Pornografia; Sexualidade; Geopolítica dos desejos; Interseccionalidade; Pornography; Sexuality; Geopolitics of desires; Intersectionality; Pornografía; Sexualidad; Geopolítica de los deseos; Interseccionalidad; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS